Optimized standby rate reduces the ventricular rate variability in pacemaker patients with atrial fibrillation. - Greenhut SE; Fraser J; Steinhaus B; Feld G; Hughes W (Pacing & Clinical Electrophysiology, 1996)
Patients with chronic atrial fibrillation (AF) and symptomatic bradycardia often receive ventricular-based pacemakers. However, many of these patients continue to have symptoms .of palpitations, which may be due to ventricular rate variability. It has previously been shown that continuous ventricular pacing during AF has a stabilizing effect on the ventricular rate. Hence, a study was initiated to determine whether a patient-specific optimal ventricular standby rate that reduces the ventricular rate variability, without over-pacing, could be predicted. A ventricular rate stabilization (VRS) pacing algorithm that increases the pacing rate until instability is reduced below a threshold was developed. The VRS algorithm was utilized to determine a patient-specific standby rate in 15 patients with chronic AF, intact AV nodal conduction, and implanted pacemakers. The computer algorithm controlled a pacemaker programmer to automatically change the pacemaker's ventricular pacing rate via telemetry. Patients were studied for 15 minutes with VRS and for 15 minutes with 50 ppm fixed rate pacing (control). The results were as follows: (1) VRS versus control = P < 0.05; (2) mean ventricular pacing rate (ppm): 77 ± 13 versus 50 ± 0; (3) mean ventricular rate (beats/min): 82 ± 13 versus 79 ± 12; (4) ventricular rate coefficient of variation (%): 11 ± 1 versus 22 ± 5; (5) percent pacing: 75 ± 8 versus 6 ± 8; (6) percent of RR intervals less than minimum pacing interval eliminated: 58 ± 12; (8) regression analysis: mean VRS pacing rate (beats/min) = 0.96 mean control ventricular rate + 2.3, r² = 0.85. We concluded that: (1) a moderate increase in the ventricular pacing rate was required to substantially stabilize the ventricular rate; (2) the resulting mean ventricular rate increased marginally; (3) a majority of RR cycles less than each patient's minimum pacing interval were eliminated; and (4) there was a linear relationship between the mean ventricular rate during control and the optimal ventricular pacing rate. Thus, a ventricular pacing rate close to the mean ventricular rate during control consistently reduced the ventricular variability. Although pacing at an increased ventricular standby rate reduces variability at rest, the optimal solution would likely be an adaptive rate algorithm that changes the ventricular standby rate as the mean intrinsic rate varies.